2020
DOI: 10.3390/cancers12040974
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Promotes Tumor Microvessel Growth via Endoglin and Extracellular Signal-Regulated Kinase Signaling Pathway and Enhances the Anticancer Efficacy of Gemcitabine against Lung Cancer

Abstract: The synergistic anticancer effect of gemcitabine (GEM) and resveratrol (RSVL) has been noted in certain cancer types. However, whether the same phenomenon would occur in lung cancer is unclear. Here, we uncovered the molecular mechanism by which RSVL enhances the anticancer effect of GEM against lung cancer cells both in vitro and in vivo. We established human lung adenocarcinoma HCC827 xenografts in nude mice and treated them with GEM and RSVL to detect their synergistic effect in vivo. Tumor tissue sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…At the same time, resveratrol can induce apoptosis and autophagy of lung adenocarcinoma cells by up-regulating the P53 level ( Fan et al, 2020 ). When used in combination with gemcitabine (GEM), resveratrol has synergistic anticancer effects ( Qin et al, 2020 ). Genistein exists in various plants for human and animal consumption, and it can inhibit the proliferation and induce apoptosis of A549 cells ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, resveratrol can induce apoptosis and autophagy of lung adenocarcinoma cells by up-regulating the P53 level ( Fan et al, 2020 ). When used in combination with gemcitabine (GEM), resveratrol has synergistic anticancer effects ( Qin et al, 2020 ). Genistein exists in various plants for human and animal consumption, and it can inhibit the proliferation and induce apoptosis of A549 cells ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, diluted primary antibodies targeting CYP27C1 (1:800, GTX45438, Gene Tex, Irvine, CA, USA), beta-actin (1:, A5441, Sigma Aldrich, St. Louis, MO, USA), phospho-tyrosine (1:2000, #9416, Cell Signaling Technology, Danvers, MA, USA), ERK1/2 (1:1000, #9102, Cell Signaling Technology), phosphorylated ERK1/2 Thr202/Tyr204 (1:2000, #4370, Cell Signaling Technology), Akt (1:1000, #4691, Cell Signaling Technology), phospho-Akt Ser473 (1:1000, #9271, Cell Signaling Technology), and p53 (1: 1000, sc-6243, Santa Cruz Biotechnology) were applied to probe the protein on PVDF membrane at four degrees Celsius overnight, following by the reaction with secondary anti-mouse or anti-rabbit antibodies at room temperature for two hours. Targeted proteins were detected using Enhanced Chemiluminescence Detection Reagents (GE Healthcare, Boston, MA, USA) and capture by Chemiluminescent Imaging System (Tanon 5200, Shanghai, China) [ 60 ]. Grey scales were analyzed by Gel-Pro ANALYZER.…”
Section: Methodsmentioning
confidence: 99%
“…Stable CYP27C1-knockdown A549 and H1975 cells, stable CYP27C1-overexpressed H460 cells, and the corresponding control cells were seeded in 96-well plates. Cell viability was tested by a 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay at 12,24,36,48,60,72,84, and 96 h after cell seeding, following the manufacturer's protocol (Promega, Madison, WI, USA), and the absorbance was measured by a microplate photometer (Thermo Fisher Scientific, Waltham, MA, USA) at 492 nm.…”
Section: Determination Of the Effects Of Cyp27c1 On Cell Proliferationmentioning
confidence: 99%
“…Qin et al. ( 95 ) recently showed that Resveratrol (RSVL) combined with Gemcitabine (GEM) has stronger tumor growth inhibition than GEM alone. In terms of mechanism, this study suggests that RSVL promotes tumor microvascular growth by down-regulating expression of endothelin and activating the ERK signaling pathway, leading to increased blood perfusion and increased drug entry into the tumor, ultimately enhancing the anticancer effect of GEM.…”
Section: Novel Anti-angiogenesis Strategies In Lung Cancer Treatmentmentioning
confidence: 99%